Diversity and Distribution of Pteridophytic flora of Punyagiri hill, Vizianagaram District, Andhra Pradesh, India - .V.S. N. Dora, G. M. Narasinha Rao, P. Prayaga Murty*, D. Srinivasa Rao, S V (Current Botany, 2011)
The present paper deals with the diversity and distribution of Pteridophytic flora in Punyagiri hill. It is located 180 06’ 70",180 06’ 68",latitudes and 830 06’ 72",830 06’ 40" longitudes , 55 km away from Visakhapatnam. Quadrate method was adopted to calculate the IVI. Sampling was carried out with 0.5x0.5m2 quadrate; fifteen quadrate samples were taken in three seasons. A total no of 13 species belonging to 10 genera and 9 families were recorded. Maximum relative density was reported for Selaginella involvense (10.6) and Pteris vittata (8.4). Minimum relative density and relative frequency were reported in the species Nephrolepis cordifolia(5.5) and Pteris pellucida (6.3). The maximum IVI was reported in Selaginella involvens (30.2) fallowed by Pteris vittata (26.2), Adiantum lunulatum(25.4), Pleopeltis pallida (24.5) and minimum in Nephrolepis cordifolia (18.6). It is concluded that the population of Pteridophytes in this region is heterogeneous.